Sequential Lonsdaleite to Diamond Formation in Ureilite Meteorites via In Situ Chemical Fluid/Vapor Deposition - Tomkins, Andrew G.; Wilson, Nicholas C.; MacRae, Colin; Salek, Alan; Field, Matthew R.; Brand, Helen E. A.; Langendam, Andrew D.; Stephen, Natasha R.; Torpy, Aaron; Pintér, Zsanett; Jennings, Lauren A.; McCulloch, Dougal G. (Proceedings of the National Academy of Sciences - PNAS, 2022)
Ureilite meteorites are arguably our only large suite of samples from the mantle of a dwarf planet and typically contain greater abundances of diamond than any known rock. Some also contain lonsdaleite, which may be harder than diamond. Here, we use electron microscopy to map the relative distribution of coexisting lonsdaleite, diamond, and graphite in ureilites. These maps show that lonsdaleite tends to occur as polycrystalline grains, sometimes with distinctive fold morphologies, partially replaced by diamond + graphite in rims and cross-cutting veins. These observations provide strong evidence for how the carbon phases formed in ureilites, which, despite much conjecture and seemingly conflicting observations, has not been resolved. We suggest that lonsdaleite formed by pseudomorphic replacement of primary graphite shapes, facilitated by a supercritical C-H-O-S fluid during rapid decompression and cooling. Diamond + graphite formed after lonsdaleite via ongoing reaction with C-H-O-S gas. This graphite > lonsdaleite > diamond + graphite formation process is akin to industrial chemical vapor deposition but operates at higher pressure (∼1–100 bar) and provides a pathway toward manufacture of shaped lonsdaleite for industrial application. It also provides a unique model for ureilites that can reconcile all conflicting observations relating to diamond formation.